CYP51A1 Induced by Growth Differentiation Factor 9 and Follicle-Stimulating Hormone in Granulosa Cells Is a Possible Predictor for Unfertilization - Nakamura, Tomoko (Reprod Sci, 2015)
Growth differentiation factor 9 (GDF9), an oocyte-secreted factor, whose receptors exist in granulosa cells, is involved in follicle progression. Therefore, GDF9 is considered to potentially mediate signals necessary for follicular growth. However, the effect of GDF9 on human granulosa cells is not fully understood. Human immortalized nonluteinized granulosa cell line (HGrC1) which we have previously reported was stimulated with GDF9 and/or follicle-stimulating hormone (FSH). Granulosa cells obtained from in vitro fertilization (IVF) patients were also evaluated with quantitative reverse transcription polymerase chain reaction (RT-PCR). Real-time RT-PCR showed that GDF9 increased messenger RNA (mRNA) levels of enzymes required for cholesterol biosynthesis, such as 3-hydroxy-3-methylglutanyl-CoA synthase 1 (HMGCS1), farnesyl-diphosphate farnesyltransferase 1, squalene epoxidase, lanosterol synthase, and cytochrome P450, family 51, subfamily A, polypeptide 1 (CYP51A1). A greater increase in mRNA levels of HMGCS1 and CYP51A1 was observed by combined treatment with GDF9 and FSH. Clinical samples showed a significant increase in CYP51A1 mRNA in the group of granulosa cells connected with unfertilized oocytes. Our results suggest that GDF9, possibly with FSH, may play significant roles in the regulation of cholesterol biosynthesis and the expression of CYP51A1 which might be a predictor for unfertilization.